(untitled) (Research, Society and Development, 2020)
Caries and periodontitis are the main problems faced by dentists in their daily lives. The biological development of such pathological processes is caused by multifactors, such as the increase in the rate of cariogenic bacteria, such as Streptococcus mutans (S. mutans) and periodontopathogenic, such as Porphyromonas gingivalis (P. gingivalis). Objective: To carry out a narrative literature review in order to analyze the methods used by several authors to reduce the index of S. mutans and P. gingivalis in the oral cavity and the consent of innovations used in the dental field. Methodology: A literature search was carried out through the electronic database PubMed, using MeSH terms. The articles were evaluated for inclusion and exclusion criteria pre-established by 04 independent researchers. Data extraction, tabulation and detailed analysis of all selected articles were performed. Results and Discussion: With the selection of 11 articles, it became evident the existence of studies that proved the reduction of S. mutans by herbal medicines and mouthwashes, however, this does not apply to P. gingivalis, with little clinical and laboratory literature. focused on such a bacterium. Final Considerations: For cariogenic bacteria, the effectiveness of methods with medicinal plants and mouthwashes with green tea in reducing the biofilm on the tooth surface became evident. Regarding periodontopathogenic bacteria, the literature highlights the importance of using antibiotics to reduce P. gingivalis, however, it is worth emphasizing the increase in bacterial resistance and the need for further research in the search for alternative methods to control these bacteria.